The Role of Leadership in Building Sports Education Management Based on Philosophy of Science: A Theoretical and Practical Study - Lestari, Widia Dwi; Ahmad, Masduki; Suryadi, Suryadi (Journal Coaching Education Sports, 2025)
Leadership in the context of education has a crucial role in determining policy direction, decision-making, and creating an environment conducive to meaningful learning. Philosophy of science, as an epistemological and axiological foundation, provides a conceptual framework that can help educational leaders understand the nature of knowledge, the purpose of education, and ethics in managing educational institutions. This research aims to examine the role of leadership in building sports education management based on the philosophy of science, both from a theoretical and practical perspective. This article outlines key concepts from the philosophy of science that are relevant to sports education management and how these principles can be implemented through various leadership styles, such as transformational, visionary and situational leadership. Practically, the study also explores examples of real-life applications where the integration of strong leadership and philosophy of science can enhance the effectiveness of school management, improve the quality of teaching and encourage innovation in the educational process. The results of this study are expected to make a significant contribution to the development of a philosophy of science-based leadership model that is able to face the challenges of education in the modern era, while improving the quality of sports education management holistically.